Status-Seeking in Criminal Subcultures and the Double Dividend of Zero-Tolerance - Dur, Robert
This paper offers a new argument for why a more aggressive enforcement of minor offenses ('zero-tolerance') may yield a double dividend in that it reduces both minor offenses and more severe crime. We develop a model of criminal subcultures in which people gain social status among their peers for being 'tough' by committing criminal acts. As zero-tolerance keeps relatively 'gutless' people from committing a minor offense, the signaling value of that action increases, which makes it attractive for some people who would otherwise commit more severe crime. If social status is sufficiently important in criminal subcultures, zero-tolerance reduces crime across the board.status concerns, street crime, subcultures, penalties, zero-tolerance, broken windows policing